JENIS-JENIS KESALAHAN DAN FAKTOR PENYEBAB DALAM PENYELESAIAN MASALAH MATEMATIS DENGAN MATERI PERBANDINGAN PADA SISWA SMP MUHAMMADIYAH KUPANG KELAS VII - Bala, Sandia; Zulfikar, Ryan Nizar; Aba, Maria Martini (Program Studi Pendidikan Matematika, Universitas Muhammadiyah Kupang, 2023)
The objective of this study is to determine errors and causal factors in junior high school students in solving mathematical problems in comparative material. The descriptive qualitative method was used in this study. This study was conducted at SMP Muhammadiyah Kupang. Six students participated in this study, with two students having high abilities, two students having moderate abilities, and two students having low abilities. Written examinations centered on comparison material and interview results were used to collect data. The results of the tests and interviews were analyzed based on the indicators of the types of errors and the causal factors, namely: concept errors, principal errors and operational errors. The results showed that. (1) Student with high category abilities, made one mistake, namely an operation error, the subject was wrong in the process of calculating the final answer. (2) Students with moderate categories make mistakes, namely, prinsi errors, principle errors do not write comparison formulas when solving problems. (3) Students with low categories i.e. subjects commit misconceptions, i.e. subjects have difficulty in determining concepts from comparisons.